Causality between female fertility and female labour force participation in Asean-5 - Subramaniam, T.; Loganathan, N.; Devadason, E.S.; Majid, M. (2015)
Researches on whether female fertility determines labour force participation or vice versa have reached mixed results. A high participation of females in the labour market can reduce fertility, conversely, high female fertility can also reduce female participation in the labour market. As such, this paper sets out to answer the question of “What causes what?” Having established the existence of cointegration for individual ASEAN-5 countries using time-series data and also for a panel of ASEAN-5 countries,we found the presence of bidirectional causality between female fertility and female labour force participation. We therefore conclude that for the ASEAN-5 countries, any policies undertaken to increase female fertility will have profound impact on female labour force participation rate.